(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2018)
INTRODUCTION: To determine the epidemiological profile of the population treated in the Audiology service provided by the Metropolitan University Hospital Foundation, as a first effort to characterize the regional hearing population, which will allow contributing to the national statistics on the prevalence of hearing pathologies. METHODS: This work responds to a retrospective longitudinal study of a quantitative nature that seeks to demonstrate the prevalence of care for different hearing disorders in the audiology consultation of the Audiology service of the FHUM between 2012 and 2017. RESULTS: The results are evidenced from a statistical analysis and graphs that support the behavior of the variables, defined as age, gender, occupation, origin and results of audiological evaluations. A frequency tabulation was generated by dividing the range of the Age variable into intervals of the same width, and counting the number of data in each interval. CONCLUSIONS: It is possible to establish the need for specialists to request the basic audiological battery consisting of audiometry, speech audiometry and acoustic immittance, in order to establish complete audiological diagnoses, cross-check tests, establish the conduct to follow, evidencing the need for agreements that allow their organization and authorization.